2019
DOI: 10.4012/dmj.2018-190
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive micro-mechanical characterization of experimental direct core build-up resin composites with different amounts of filler contents

Abstract: Dual-cured resin-based composites are gaining popularity as core build-up materials. Physical and elastoplastic characteristics of new experimental core build-up materials with variable filler contents (+2.5 and +5 wt%) were investigated using classic macroexperiments and nanoindentation. Flexural fracture strength increased from 91.7±11.8 to 114.1±9.1 and 116.6±14.7 MPa in the +2.5 and +5 wt% groups, respectively; similarly, elastic moduli increased from 12.6±0.9 to 15.4±1.2 and 15.3±2.0 MPa, respectively. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(31 reference statements)
2
4
0
Order By: Relevance
“…Among the investigated DC resin composites, Gradia Core and SFRCs showed the highest values of flexural strength and modulus, which appears to be the outcome of high filler/fiber loading in comparison with the other tested materials. This is in good agreement with previous research that found a positive relationship between inorganic filler loading and flexural properties of resin composites [ 8 , 16 ]. However, the differences in flexural properties among the investigated resin composites might be attributed to variables other than filler loading ( Table 2 and Figure 5 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the investigated DC resin composites, Gradia Core and SFRCs showed the highest values of flexural strength and modulus, which appears to be the outcome of high filler/fiber loading in comparison with the other tested materials. This is in good agreement with previous research that found a positive relationship between inorganic filler loading and flexural properties of resin composites [ 8 , 16 ]. However, the differences in flexural properties among the investigated resin composites might be attributed to variables other than filler loading ( Table 2 and Figure 5 ).…”
Section: Discussionsupporting
confidence: 93%
“…Most of these materials are made of methacrylate resin and have a higher filler content and mechanical strength compared to dual-cure resin cements [ 7 ]. It is important to know that adding extra particulate-fillers improves the mechanical properties of the post-luting agent but also increases the viscosity, which in turn affects the adhesive interface integrity and leads to a deterioration of the bond strength and the potential development of microleakage [ 8 , 9 ]. In addition, the high viscosity of the material may limit it from being injected into the root canal, resulting in gaps and voids at interfaces [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the inorganic filler content and the elastic modulus had R 2 values of 0.914 (p=0.003) for the top surface and 0.725 (p=0.032) for the bottom surface. The filler content was significantly correlated to the mechanical properties of the resin composites as reported in other studies 24,28) .…”
Section: Discussionsupporting
confidence: 80%
“…Generally, mechanical properties such as the flexure strength and Vickers micro hardness of resin composites improve with an increase in filler content 1,[24][25][26] . Therefore, it is important that the inorganic filler (e.g., quartz, colloidal silica, and silica glass containing barium, strontium, and zirconium) content of resin composites be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Teeth extensively destroyed with a lost coronal structure can be used to support a restoration or other rehabilitations in order to restore function, aesthetics and comfort to the patient ( 1 - 4 ) when appropriate techniques, management and treatments are applied. Thus, post-and-core restorations are necessary depending on the degree of dental destruction, tooth affected, occlusion, root canal configuration and other clinical variables ( 3 , 5 - 7 ).…”
Section: Introductionmentioning
confidence: 99%